Including performance level lowers prevalence of non-timeloss groin injury. A cross-sectional study in 383 female amateur football players - Langhout, R. R. F. H.; Tak, I. J. R. (Physical Therapy in Sport, 2019)
Taking into account the perceptions of athletes on injury lowers the prevalence of non-timeloss groin injury by a quarter. shows a previously not documented group of non-injured players who have groin pain and normal performance. Players with groin pain and normal performance are not considered injured and show more groin-related symptoms and problems (HAGOS) than those without groin pain. less groin-related symptoms and problems (HAGOS) than those with groin pain and reduced performance (non-timeloss groin injury).